“Don't Gamble With Children's Rights”—How Behavioral Design Impacts the Right of Children to a Playful and Healthy Game Environment - van der Hof, Simone; van Hilten, Stijn; Ouburg, Sanne; Birk, Max V.; van Rooij, Antonius J. (Frontiers in Digital Health, 2022)
Gaming is an important pastime for young people to relax, socialize and have fun, but also to be challenged, show creativity and work together to achieve goals. The design of games can have an impact on their behavior. With the changing revenue models of games, we see that game design is increasingly taking forms that do not always have a positive impact on children and may interfere with, or even violate, children's rights. This article examines how evolving revenue models of games impact user's behavior via game design. Behavioral design in games thus raises questions about children's rights to play and recreation, to health, to protection from economic exploitation and to data protection.